Atividade física na adolescência e sua relação com índices de qualidade de vida, autoimagem corporal e uso de drogas - Pinheiro, Bruno de Oliveira [UNIFESP] (2015)
The growing use / abuse of legal and illegal substances among adolescents has been the subject of numerous studies, focusing not only on the prevalence of use, but also on factors associated with the risk and protection, among the levels of quality of life and physical activity, by the effect on the health of the young. OBJECTIVES: This study aimed to investigate the relationship between different levels of physical activity, self-body image, quality of life and consumption of psychotropic substances among students. METHOD: The study was conducted with 754 adolescents from four public schools selected by criteria of convenience. We used as instruments the International Physical Activity Questionnaire (IPAQ), the KIDSCREEN-27 and the Drug Use Screening Inventory (DUSI), beyond a sociodemographic questionnaire with information related to academic aspects and the perception of self-body image, all self-applicable. The data underwent descriptive analysis and hypothesis testing, mean and variance based on test Kolmorov-Smirnov. The data underwent descriptive analysis and hypothesis testing. To compare the groups used the Student t test for continuous variables and the chi-square test for categorical variables. RESULTS: In relation to the level of physical activity, 33% of the sample practiced low, 51% moderate and 16% high level. Compared to other groups, students of the high level of physical activity group had lower levels of quality of life in dimensions related to autonomy / relationship with parents, friends / social support and school performance and higher use of drug use, energy drinks and ergogenic. By linking physical activity and perception of self-body image, the findings highlight the rates of body satisfaction in boys and body dissatisfaction in girls. It was indicative of abuse and dependence on substances in boys satisfaction in and dissatisfaction girls. For both sexes, the rate dissatisfied practicing high level of physical activity was higher compared to the other groups. CONCLUSIONS: The results found here consider that the use of substances can also be associated with the practice of physical activities, even if considered healthy practices, undermining its effectiveness as a protective factor when excessive practice of physical activity becomes risky behavior for use drug and negatively affecting the adolescent's quality of life and their perception of body self-image.